1,1 `-{[1,4-Phenylenebis(methylene)]bis(oxy)bis(4,1-phenylene)}diethanon e - Al-Mohammed, N.N.; Alias, Y.; Abdullah, Z.; Khaledi, H. (International Union of Crystallography, 2011)
The centroid of the central aromatic ring of the title molecule, C(24)H(22)O(4), is located on an inversion center. The dihedral angle between the central and terminal benzene rings is 75.00 (7)degrees. In the crystal, molecules are linked through C-H center dot center dot center dot O hydrogen bonds into chains along [121]. The chains are connected into layers via C-H center dot center dot center dot pi interactions.